Development of Animation Video Learning Media to Improve Class XI Science Students’ Understanding - Sarina; Army Auliah; Hardin (Universitas Negeri Medan, 2024)
This research and development (R&D) aim to produce valid, practical and effective animated video learning media. The research subjects are divided into two parts, namely the first part of the product design validation subject or expert test conducted by 2 material experts and 1 media expert and the second part of the product trial subject conducted by testing the learning media in class XI IPA 3 and 2 class XI teachers of SMA Negeri 1 Gowa as observers. This learning media has been validated, has been tested limitedly and revised. The results of this study are: (1) validation by media experts of 3.4 with very valid criteria and (2) validation by material experts of 3.79 with very valid criteria. Animated video media based on the implementation test, teacher and student responses with an average percentage score of 88%, 86.11% and 86% respectively. For animated video media, the effectiveness criteria are in the very high category, with student learning outcomes meeting the effective criteria (≥80%), where the class completion percentage is 88.8%. Animated video learning media developed using the ADDIE model is suitable (valid, practical and effective) for use in learning.